Platelet-rich plasma for the treatment of diabetic foot ulcer: a systematic review - OuYang, Hong; Tang, Yi; Yang, Fan; Ren, Xin; Yang, Jing; Cao, Hongyi; Yin, Yifan (Frontiers in Endocrinology, 2023)
Background ：With the increasing incidence of diabetes, diabetic foot ulcer(DFU) has become one of the most common and serious complications in people with diabetes. DFU is difficult to promote wound healing with conventional therapies or antibiotics, whereas platelet-rich plasma(PRP) can promote wound healing by releasing various bioactive molecules stored in platelets, making it more promising than traditional antibiotics. Therefore, the purpose of this systematic review is to summarize and analyze the efficacy of PRP in the treatment of DFU.A literature search was undertaken in PubMed, CNKI, EMB-ASE, the Cochrane Library, the WanFang Database and the WeiPu Database by computer. Included controlled studies evaluating the efficacy of PRP in the treatment of diabetic foot ulcers.The data extraction and assessment are on the basis of PRISMA.Results: Twenty studies were evaluated, and nineteen measures for the evaluation of the efficacy of PRP in DFU treatment were introduced by eliminating relevant duplicate measures.The efficacy measures that were repeated in various studies mainly included the rate of complete ulcer healing, the percentage of ulcer area reduction, the time required for ulcer healing, wound complications (including infection rate, amputation rate, and degree of amputation), the rate of ulcer recurrence, and the cost and duration of hospitalization for DFU, as well as subsequent survival and quality of life scores.One of the most important indicators were healing rate,ulcer area reduction and healing time.The meta-analysis found that PRP was significantly improve the healing rate(OR ＝ 4.37 ， 95% CI 3.02-6.33, P < 0.001) and shorten the healing time(MD＝-3.21, 95% CI -3.83 to -2.59,P < 0.001)of patients with DFU when compared to the conventional treatment,but there was no significant difference in reducing the of ulcer area(MD＝5.67, 95% CI -0.77 to 12.11,P =0.08＞0.05 ).The application of PRP to DFU can improve ulcer healing rate and shorten ulcer healing time, but more clinical data are needed to clarify some efficacy measures.At the same time,a standardized preparation process for PRP is essential.